Determinants of Cash Holding: An Empirical Study of Non-Cyclical Consumer Companies on the Indonesia Stock Exchange - Urahmah, Cut Tifani; Meutia, Rita; Fuadi, Raida (Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of net working capital, growth opportunity, and leverage on cash holding in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The results show that simultaneously, net working capital, growth opportunity, and leverage have a significant effect on cash holding. Partially, net working capital has a significant positive effect on cash holding while growth opportunity has no effect on cash holding, and the leverage variable has a negative effect on cash holding. Future research is recommended to cover more industrial sectors as well as a longer period of time and can add other variables using different analytical methods.